NUMERICAL ASSESSMENT OF SEISMIC STRENGTHENING OF A FULLY FILLED VERTICAL STEEL OIL STORAGE TANK USING CIRCUMFERENTIAL STIFFENING RIBS (Western European Journal of Modern Experiments and Scientific Methods, 2026)
This study presents technical solutions aimed at reducing the seismic vulnerability of existing storage tanks. Scientific and engineering proposals are developed to enhance the seismic resistance of the tank, and structural strengthening measures are formulated based on numerical analyses performed using the LIRA-SOFT 10.12 software package.